Analisis Pemanfaatan Tiktok Sebagai Media Dakwah (Studi Pada Mahasiswa IAIN Manado) - Muhammad Zidane Kendju Kendju; Shinta Nento; Aris Soleman (Ahsan: Jurnal Dakwah dan Komunikasi, 2022)
This paper examines the analysis of the use of Tiktok as a medium for da'wah (study on IAIN Manado students). This study aims to find out, analyze, and describe the form of using Tiktok in general and the form of using Tiktok as a medium for proselytizing in IAIN Manado students. The research method used in this study is a type of field research that intends to understand the facts in the research object with a descriptive-qualitative approach with data collection methods in the form of observation, interviews, and documentation. The data obtained are then analyzed qualitatively through data reduction, presentation, and conclusion.The study’s results explained that Tiktok media, in general, is intensely used by students as a means of entertainment, information, and educational media. Specifically, the use of Tiktok for education in the context of instilling Islamic values through proselytizing content is quite intensely utilized by IAIN Manado students. Tiktok is seen as effective as a proselytizing medium if it is used continuously and efficiently as a proselytizing medium because it is quite accessible to students as long as the content cannot be separated from the context of Islamic teachings. Keywords: Utilization Analysis; Tiktok; Da'wah; IAIN Manado